Slovenia’s social uprising in the European crisis: Maribor as periphery from 1988 to 2012 - Kirn, Gal (Stasis, 2014)
This article contextualizes the recent social uprisings in Maribor as a political articulation of the periphery in both the local Slovenian and the more general European context. The case of Maribor is of particular interest to anyone who wants to excavate different temporalities within “transition”: Maribor is not only the name of a failed capitalist de-industrialization, but was, 25 years ago, also the site of a failed socialist industrialization. My thesis explores the continuity and discontinuity of Maribor as a privileged site of popular resistance, while on a more theoretical level, it presents the unfolding of politics of dissensus. The author uses Rancière’s concept of “the people” as the most adequate figure for addressing the specificity of the most recent struggles. Also, the question of “periphery” as the site of utmost importance for contemporary political imagination and experimentation is brought to the reader’s attention.